Governance of academic medical centres in changing healthcare systems: An international comparison - Cardinaal, Ester; Dubas-Jakóbczyk, Katarzyna; Behmane, Daiga; Bryndová, Lucie; Cascini, Fidelia; Duighuisen, Heleen; Davidovitch, Nadav; Waitzberg, Ruth; Jeurissen, Patrick (Health policy, 2022)
We provide an explorative and international comparison of the governance models of academic medical centres (AMCs). These centres face significant challenges, including disruptive external pressures and enduring financial conflicts pertaining to patient treatment, research and education. Therefore, we covered 10 European countries (Cyprus, Czechia, Denmark, Germany, Italy, Latvia, the Netherlands, Norway, Poland and Spain) and one associated state (Israel) in our analysis. In addition, we developed an expert questionnaire to collect data on the governance of AMCs in these 11 countries. Our results revealed no standardised definition of AMCs, with countries combining patient care, education/teaching and research differently. However, the ownership of such institutions is significantly homogeneous and is limited to public or private, nonprofit ownership. Furthermore, significant differences are associated with the (functional) integration level between the hospital and medical school. Therefore, most experts believe that the governance of AMCs will evolve into a more functionally integrated model of patient care, research and education.
Keywords: vysokoškolská lékařská centra; Germany; Academic Medical Centers; Italy; poskytování zdravotní péče; lidé; Kypr; Itálie; Delivery of Health Care; Humans; Německo; Cyprus